2018
DOI: 10.1017/aer.2018.46
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of the synergy of Composite Cycle and intercooled recuperation

Abstract: The synergistic combination of two promising engine architectures for future aero engines is presented. The first is the Composite Cycle Engine, which introduces a piston system in the high pressure part of the core engine, to utilise closed volume combustion and high temperature capability due to instationary operation. The second is the Intercooled Recuperated engine that employs recuperators to utilise waste heat from the core engine exhaust and intercooler to improve temperature levels for recuperation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…The framework features high flexibility with regards to the synthesis and simulation of unconventional thermodynamic cycles and novel power plant system architectures. While a basis for the FP-CCE simulation and integration has been established already by conceptual design studies of different variants of the CCE concept in the past [15][16][17][18], numerical simulation of the steam injecting engine concept entails further efforts. Indeed, the steam injecting engine concept requires the implementation of additional specific components like steam generator, condenser, liquid water recovery system and pump.…”
Section: Development Of Methodsmentioning
confidence: 99%
“…The framework features high flexibility with regards to the synthesis and simulation of unconventional thermodynamic cycles and novel power plant system architectures. While a basis for the FP-CCE simulation and integration has been established already by conceptual design studies of different variants of the CCE concept in the past [15][16][17][18], numerical simulation of the steam injecting engine concept entails further efforts. Indeed, the steam injecting engine concept requires the implementation of additional specific components like steam generator, condenser, liquid water recovery system and pump.…”
Section: Development Of Methodsmentioning
confidence: 99%
“…The high-pressure compression the high scavenging efficiency in the piston engine, and the following isochoric combustion can lead to significant improvements in efficiency. Kaiser [45] conducted some initial studies on the FP-CCE concept and reports that the overall pressure ratio of this engine can go up to 32.4 at top of climb condition of the aircraft with a maximum thrust specific fuel ratio of 12.78 g/kN-s. It is also reported that at cruise condition, the piston engine NOx emission index estimate is approximately 139.7 g/kg of fuel, and for the sequential combustor, it is 1.3 g/kg of fuel This concept is still in its early stages of development and further studies are required to solve issues of mechanical and scavenging losses, lubrication, mass and size, control, NOx emissions, pulsating flow, and vibrations.…”
Section: Figure 5: Schematic Of a Fp-cce [44]mentioning
confidence: 99%